Utilization Social Media for MSME Development - Henky Hendrawan; Soni Suharmono; Sulistyo Budi Utomo; Sonny Santosa; Rini Novianti (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to explain the importance of socialization and social media utilization in the development of micro, small, and medium-sized enterprises (MSMS) in Sukabumi district. Social media has become a very effective tool in building customer relationships, marketing products, and increasing business visibility. However, there are still many MSMSs in Sukabumi district that have not exploited the potential of social media optimally. Through socialization, MSMS owners will be given a better understanding of social media and how to use it as an effective marketing tool. This socialization will involve training and enhancement of knowledge about relevant social media platforms, online marketing strategies, creating interesting content, as well as measurement and analysis of social media performance. It is expected that with the socialization of this social media utilization, the MSMS in Sukabumi district will be able to use social media better to promote their products and services, reach a wider audience, and increase their online presence. With increasing online presence, it is anticipated that there will be an increase in MSMS's turnover and overall growth in the Sukabomi district.